2012
DOI: 10.1590/s0102-311x2012000700012
|View full text |Cite
|
Sign up to set email alerts
|

Uso de anti-hipertensivos e antidiabéticos por idosos: inquérito em Belo Horizonte, Minas Gerais, Brasil

Abstract: Concern over the harmful effects of drug use by the elderly has motivated studies aimed at identifying problems in such utilization. This was a household survey with retirees aged > 60 years living in Belo Horizonte, Minas Gerais State, Brazil, in 2003, who reported having a diagnosis of diabetes and/or hypertension. Quality of anti-hypertensive and anti-diabetic medication was measured by redundancy, combinations of drugs, and inappropriate drugs. Among 283 elderly patients (89%) with self-reported hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
22

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 16 publications
2
17
0
22
Order By: Relevance
“…When analyzing adherence to drug treatment, it was found that 22.8% exhibited non-adhesive behavior, numbers slightly greater than a study carried out in Belo Horizonte (Minas Gerais), where non-adherents represented 22.5% of the sample 21 .…”
Section: Discussionmentioning
confidence: 56%
“…When analyzing adherence to drug treatment, it was found that 22.8% exhibited non-adhesive behavior, numbers slightly greater than a study carried out in Belo Horizonte (Minas Gerais), where non-adherents represented 22.5% of the sample 21 .…”
Section: Discussionmentioning
confidence: 56%
“…Hypertension is a treatable disease and, when properly controlled, the development of symptomatic cardiovascular disease can be delayed or even prevented 4 . Among the strategies aimed at controlling these diseases, there is drug treatment, which, when properly conducted, enables the control of diseases, reduces their morbidity and mortality, and improves the quality of life of users 5 . The Strategic Action Plan to Combat Chronic Non-Communicable Diseases (NCDs in Brazil), 2011 -2022, actions and investments needed to cope with such diseases were defined and prioritized.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Dentre os fatores de risco para o desenvolvimento das doenças crônicas não-transmissíveis, a hipertensão arterial sistêmica (HAS) é o mais prevalente. [8][9][10] A HAS é definida como a manutenção de níveis de pressão arterial acima de 140 mmHg na sistólica e 90 mmHg na diastólica. 11 Está relacionada a fatores intrínsecos, como hereditariedade, sexo, idade e raça; e a fatores extrínsecos, como tabagismo, sedentarismo, obesidade, estresse, dislipidemia e dieta.…”
Section: Introductionunclassified
“…8 A HAS é um importante problema de saúde pública, visto que a morbimortalidade e os custos com o seu tratamento são elevados. 9,13 Por ser muitas vezes assintomática, há dificuldades para que os indivíduos procurem os serviços de saúde para o diagnóstico e adesão ao tratamento.…”
Section: Introductionunclassified